2020
DOI: 10.5114/ada.2020.96254
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of air pollution on exacerbations of allergic asthma in Užice region, Serbia

Abstract: Introduction: Many time-series studies have shown a positive association between air pollution and asthma exacerbation. However, till now only one study in Serbia has examined this relationship. Aim: To examine the associations between air pollution and asthma emergency department (ED) visits in the Užice region, Serbia. Material and methods: A time-stratified case-crossover design was applied to 424 ED visits for asthma exacerbation that occurred in the Užice region, Serbia, in 2012-2014. Data about ED visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
2
0
3
Order By: Relevance
“…Of these, 70 fulfilled the inclusion criteria (figure 1). 7 21–26 34–96 Of the 70 included studies, 56 estimated the short-term effects of BC/EC using a time series design or case cross-over design, while 14 studies explored the long-term effects of BC/EC using a cohort design. Thirty-seven of the 70 studies reported morbidity as the outcome variable, 25 studies reported mortality and 8 studies reported both morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 70 fulfilled the inclusion criteria (figure 1). 7 21–26 34–96 Of the 70 included studies, 56 estimated the short-term effects of BC/EC using a time series design or case cross-over design, while 14 studies explored the long-term effects of BC/EC using a cohort design. Thirty-seven of the 70 studies reported morbidity as the outcome variable, 25 studies reported mortality and 8 studies reported both morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The confounding bias and selective reporting were mostly rated as ‘probably low’. However, seven studies were rated as ‘probably high’ risk because not all critical potential confounders were adjusted in the analysis 7 24 26 46 55 74 91. In addition, the majority of the included studies on the exposure assessment were assessed as ‘probably low’ and ‘probably high’, and in some cases studies were rated as ‘high’ risk.…”
Section: Resultsmentioning
confidence: 99%
“…Tampoco Kovacevic et al, en un estudio desarrollado en Serbia, encontraron una asociación significativa. Estos autores reportaron un valor de OR elevado (1,76), pero al incluir una muestra pequeña de 424 VUA, los intervalos de confianza eran muy amplios 121 .…”
Section: Contaminantes Y Exacerbaciones Por Asma 132511 Pm25unclassified
“…VUA: visitas a urgencias por asma; Lag: desfase entre la exposición y la visita a urgencias; IC95%: intervalo de confianza al 95%; MLG: modelo lineal generalizado; CC: casos cruzados; RR: riesgo relativo; OR: Odds ratio *Oredenadas por nivel decreciente de concentración3 , no encontrando una asociación positiva significativa entre el número de VUA y PM10 (asociación negativa: RR <1)120 ; mientras que Kwon et alanalizando 660 VUA en Corea, con un valor medio de PM10 de 48,7 µg/m 3 , tampoco encontraron una relación significativa131 . Kovacevic et al analizó una serie de 424 VUA en Serbia, con un nivel medio de PM10 de 34,2 µg/m 3 , reportando una relación significativa entre el aumento de este contaminante y las VUA solamente en el subgrupo de pacientes con rinitis alérgica, pero no en la población total121 . Con respecto a los meta-análisis, Zheng et al incluyeron 51 publicaciones que analizaban esta relación, encontrando una asociación positiva significativa con un RR de 1,010 por 10 µg/m 3 , mientras que observaron un tamaño de efecto ligeramente menor para el subgrupo de población adulta en los 7 estudios analizados (RR 1,009)115 .…”
unclassified
See 1 more Smart Citation